High resolution secondary ion mass spectrometry analysis of boron in high strength steels and polycrystalline superalloys - Mohd Yusof, HA (2020)
Boron is added to high strength steels to increase hardenability and as grain strengthener in polycrystalline superalloys, but is difficult to study by many conventional techniques. The main aim of this study was to explore the application of high resolution secondary ion mass spectrometry (NanoSIMS) to analyse boron distributions in a range of high strength steels after different commercial heat treatments. New findings on the behaviour of boron at four stages of the manufacturing process (as-rolled, as-quenched, quenched and tempered and direct quenched) are demonstrated, and particularly information on how Ti plays an important role in maximising the beneficial effect of boron on hardenability. Boron was found to segregate at prior austenite grain boundaries during isothermal heat treatments by equilibrium segregation, and also during cooling by non-equilibrium segregation. In hot rolled samples, boron particles started to precipitate out during the hot rolling process, and during subsequent air cooling boron also segregated to prior austenite grain boundaries. Strong grain boundary segregation was observed in the as-quenched samples, with small precipitates near the grain boundaries as well as in the grain interiors. Finally, in quenched and tempered samples, small boron-containing precipitates were created during the tempering stage that were not visible in other samples. A longer heating time in the austenite region also gives higher boron segregation at grain boundaries. As a result, the direct quenching method can be an alternative process to reduce costs and increase overall efficiency in steel manufacturing as it shows a similar boron distribution to that developed by the conventional thermomechanical process. As well as these qualitative observations, quantitative analysis of boron segregation to a large number of grain boundaries has been demonstrated using the NanoSIMS, because it can map large areas in a short time. This is the only extensive quantification of grain boundary segregation performed with a NanoSIMS instrument to date with 100s of grain boundaries analysed. Quantification of boron-containing precipitate densities and size has also been reported. In another set of experiments on samples of a new polycrystalline Ni superalloy, the primary effect of boron addition has been shown to be the suppression of Cr-rich M23C6 carbides and the formation of Cr-rich M5B3 borides. NanoSIMS analysis of these superalloys was shown to provide complementary information to SEM, APT and TEM studies carried out by other researchers on the same alloys. The data presented in this thesis shows that NanoSIMS can be added to and can complement conventional techniques to guide the development of materials for industrial applications and understand the affect that heat treatments have on microstructure and materials properties.